2010
DOI: 10.1002/gps.2668
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐defined vascular depression: a review of the construct

Abstract: Despite considerable data supporting the validity of MRI-defined vascular depression, there are a number of critical issues that remain, including establishing a causal relationship between cerebrovascular disease and late-life depression, establishing consistent diagnostic criteria, determining the importance of lesion type and location, and understanding the course of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 104 publications
(152 reference statements)
0
24
0
3
Order By: Relevance
“…33,36 Many studies have also found high rates of cerebrovascular disease and white matter hyperintensities (WMH) on MRIs in depressed elderly patients. 37 …”
Section: Contributors To Elder Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,36 Many studies have also found high rates of cerebrovascular disease and white matter hyperintensities (WMH) on MRIs in depressed elderly patients. 37 …”
Section: Contributors To Elder Depressionmentioning
confidence: 99%
“…They are characterized by arteriosclerosis, perivascular demyelination, dilated periventricular spaces, and ischemia. 45,46 WMHs can predispose individuals to depression 32,37 by disrupting the fiber tracts connecting cortical and subcortical structures, 32 including tracts in the dorsolateral prefrontal cortex and the anterior cingulate cortex. 45 They are frequently found in patients with late-life depression.…”
Section: Contributors To Elder Depressionmentioning
confidence: 99%
“…This is also critical for clinical practice, as both conditions (depression and cerebrovascular disorders) are becoming more prevalent with the ageing population. Nevertheless, although previous (systematic and comprehensive) reviews evaluated construct validity, 14 biological plausibility, 1 causality, 15 neuroimaging findings 16 and discriminant validity, 17 none, to the best of our knowledge, scrutinized the VaD concept for interventional studies. Therefore, we systematically reviewed all studies proposing therapeutic interventions for VaD.…”
Section: Introductionmentioning
confidence: 97%
“…Birçok çalışma, ileri yaşta görülen depresyonda klinik ve nörogörüntüleme kanıtları ile serebrovasküler değişiklikleri tespit etmeye çalışmıştır (25). Bu çalışmaların birçoğunda ileri yaş depresyonunda, aynı yaştaki kontroller ile karşılaştırıldığında, MR değişikliklerinin daha fazla olduğu ortaya konmuştur (26).…”
unclassified
“…Derin beyaz madde hiperintensitelerinin sadece ileri yaş depresyonu ile değil, aynı zamanda geç başlangıçlı depresyon ile de ilişkili olduğu düşünülmektedir (25). Geç başlangıçlı depresyon, başlangıç yaşı üzerinde tam bir fikir birliğine varılamamışsa da, ilk depresyon epizodunun ileri yaşlarda görülmesi ile karakterize, erken yaşta başlayıp ileri yaşta tekrarlarla seyreden depresyondan farklı bir tabloyu ifade eden bir klinik tanımlamadır (30,31).…”
unclassified